1980
DOI: 10.1016/0309-1651(80)90177-0
|View full text |Cite
|
Sign up to set email alerts
|

The ultrastructure of centriole in mammalian tissue culture cells

Abstract: Structural polarity of centriole has been shown by analyzing serial sections of centrioles in the tissue culture cells of mouse, man, pig and Chinese hamster. Its major component is nine microtubule triplets. The inclination of the triplets towards the radius at the proximal end of the centriole is smaller than at the distal one. The internal tubule of the triplet has a smaller diameter than the middle and external ones; The triplets are bound by links of various nature all over their length. In the middle par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
31
0

Year Published

1982
1982
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 3 publications
5
31
0
Order By: Relevance
“…At the site where the centriole transforms into a cilium, there is no basal plate that is typical of kinocilia . The appendages locate strictly symmetrically, compared with the cilum-free centrioles the structure of which we described previously (34).…”
Section: Resultsmentioning
confidence: 58%
See 1 more Smart Citation
“…At the site where the centriole transforms into a cilium, there is no basal plate that is typical of kinocilia . The appendages locate strictly symmetrically, compared with the cilum-free centrioles the structure of which we described previously (34).…”
Section: Resultsmentioning
confidence: 58%
“…Selected interphase cells were identified in light micrographs. Rotational photos were prepared as described previously (34) . To measure the centriole tilt towards the section plane, we made, for comparison, photos of the perpendicular section of the centriole using a microscope with a goniometer (Philips-401) at various tilt angles of the section plane.…”
Section: Methodsmentioning
confidence: 99%
“…Stubblefield and Brinkley (Stubblefield and Brinkley, 1967) described a structure in the distal lumen in centrioles in Chinese hamster fibroblasts that did not exhibit ninefold rotational symmetry. Vorobjev and Chentsov (Vorobjev and Chentsov, 1980) found a fine filament that formed an incomplete circle at the distal end of centrioles in various mammalian species. In the latter two studies, the acorn is not clearly revealed.…”
Section: Discussionmentioning
confidence: 99%
“…The mother centriole defines the site of nascent CBB assembly, the position and orientation of cilia formation and beating, the orientation of mitotic spindle poles and the maintenance of cellular geometry. During mitosis, the mother centriole is positioned within the centrosome perpendicular to the spindle axis, suggesting that the asymmetric orientation of centrioles is important for mitotic chromosome segregation (Vorobjev and Chentsov, 1980). Furthermore, proper positioning and orientation of motile cilia is required for effective ciliary beating to move fluid.…”
Section: Introductionmentioning
confidence: 99%